Food self-sufficiency versus foreign currency earnings in the Sudanese irrigated agriculture - Khalid H.A. Siddig; Amel M. Mubarak (Journal of the Saudi Society of Agricultural Sciences)
The analysis undertaken in this paper applies a multimarket model to simulate two policy measures based on the assumption that the government of Sudan would pursue two policies on the Gezira scheme the biggest irrigated scheme in Africa in attempts to achieve food self-sufficiency from wheat (major food crop), or to improve the foreign exchange earnings from cotton (major cash crop) through expanding their portions of cultivated land. The paper investigates the implications of each scenario on crops output, food self-sufficiency indicators and tenants’ welfare. Findings show that, the food security scenario raises self-sufficiency from wheat by 40% and reduces it for sorghum by 4%. However, it reduces the welfare level as the earnings from exports and revenues from tariffs decline. The foreign earning scenario on the other hand, improves the overall foreign earnings and enhances farmers’ welfare. Nonetheless, the study suggests that none of the two policies would achieve both objectives alone, hence it is recommended that, both policies are to be considered in a policy package that considers as well other related components.